The Effect of ROA, EPS, DER, and Firm Size on Stock Prices of Companies in the Food and Beverage Sector Listed on the IDX - Ayu Khoni'ah, Selvia Putri; Dewi, Nurma Gupita (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2025)
The objective of this study is to examine the impact of ROA, EPS, DER, and company size on the stock prices of food and beverage sector companies listed on the IDX. A purposive sampling method was employed, and multiple linear regression analysis indicated that ROA has a significant negative effect on stock prices. On the other hand, EPS and company size have a significantly positive impact on stock prices. Although DER exhibits a slight negative effect on stock prices, this effect is not statistically significant. The adjusted R-squared value of 0.812 suggests that ROA, EPS, DER, and company size collectively explain 81.2% of the variation in stock prices, with the remaining 18.8% attributable to other factors not included in the study model.